Indigenous mental health research in the context of climate change: methodological reflections on language and barriers to cultural practice - Victoria Pratt; Samrawit Gougsa; Nicole Redvers; Daniel Kobei; Sylvia Kokunda; Siwakorn Odochao; Jenni Laiti; Babitha George; Jessica Sim (BMJ Mental Health)
Climate change creates unique forms of psychological distress for Indigenous Peoples whose identities and cultural practices are often intrinsically connected to ancestral lands, yet research on culturally appropriate methodologies for studying Indigenous mental health in the context of climate change remains limited. This perspective paper presents methodological reflections from Land Body Ecologies research collective, which collaborates with Ogiek (Kenya), Batwa (Uganda), Iruliga (India), Pgak’yau (Thailand) and Sámi (Sápmi) Indigenous Peoples to explore climate change-related mental health impacts through the lens of solastalgia. Through participatory dialogues conducted during in-person gatherings, team members reflected on three years of community-based participatory research and identified two critical methodological challenges underexplored in the existing literature: (1) language and concept translation difficulties, where terms such as ‘mental health’ and ‘climate change’ lack direct cultural equivalents and may carry stigmatising connotations and (2) barriers to cultural practices, where climate change and conservation-related legislation restricts Indigenous Peoples’ access to ancestral lands and traditional practices essential for well-being. These challenges reflect deeper epistemological tensions between conventional research approaches and Indigenous holistic worldviews that understand land, body and ecosystems as interconnected. It concludes that meaningful mental health research with Indigenous Peoples demands active recognition of Indigenous cultural rights and self-determination, collaborative approaches that honour Indigenous knowledge systems and systemic changes that normalise Indigenous timelines, relationality and knowledge sovereignty within research institutions.